ChemInform Abstract: Inhibition of Cytokine Release by Mycobacterium tuberculosis Phenolic Glycolipid Analogues. Issue 44 (4th November 2014) - Elsaidi, Hassan R. H.; Lowary, Todd L.
Abstract Three new phenolic glycolipid analogues (I) are synthesized and evaluated for their ability to modulate cytokine and NO release.